2020
DOI: 10.1111/jfpp.14828
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and quality characteristics of gluten‐free potato cake

Abstract: Cakes are the mainstay of baked goods, have a long history and are desired by consumers all over the world (Zhang, Zhang, & Wu, 2008). Cakes can be nutritious, have a light and fluffy texture, convenience, and variety. The constant change in consumer demand has driven the research and development of food with health functions. Currently, functional cakes are mainly made from wheat flour mixed with other ingredients, to produce products such as purple potato health cake, kiwi chiffon cake, sugar-free gummy heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
4
1
Order By: Relevance
“…In a recent study in the literature, potato flour was also used as a raw material for another gluten-free product and reported to contain 9.17 % protein, 3.86 % ash, 0.26 % fat and 20.51 % dietary fiber. Therefore, proximate contents found were generally higher than the potato flour used in this study (11). In contrast, the potato flour used in another study was reported to have an ash content of 2.90 %, protein 5.47 %, total carbohydrate 79.83 % and dietary fiber 5.29 %, thus being more similar to the raw material presented in this study (39).…”
Section: Proximate Analyses Of Raw Materialscontrasting
confidence: 47%
See 2 more Smart Citations
“…In a recent study in the literature, potato flour was also used as a raw material for another gluten-free product and reported to contain 9.17 % protein, 3.86 % ash, 0.26 % fat and 20.51 % dietary fiber. Therefore, proximate contents found were generally higher than the potato flour used in this study (11). In contrast, the potato flour used in another study was reported to have an ash content of 2.90 %, protein 5.47 %, total carbohydrate 79.83 % and dietary fiber 5.29 %, thus being more similar to the raw material presented in this study (39).…”
Section: Proximate Analyses Of Raw Materialscontrasting
confidence: 47%
“…Total mass fractions of protein (6.7%), ash (2.8%) and carbohydrates (81.1%) in potato flour were slightly different with respect to the other flour sources; although the fat mass fraction was significantly higher than the other ingredients (except for the chia seeds) and the moisture mass fraction was lower (p<0.05). In a recent study ( 11 ), potato flour was also used as a raw material for another gluten-free product and reported to contain 9.17% protein, 3.86% ash, 0.26% fat and 20.51% dietary fibre. Therefore, proximate mass fractions were generally higher than in the potato flour used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cornerstone of baked foods, cakes has a long history and is popular with consumers throughout (Zhang and Wu, 2008). The addition of vitamins, minerals, polyphenols, and fibre from dietary sources is thought to be an effective way to create meals with high nutritional value (Li et al, 2020). Cakes can be nutritious, have a light and fluffy texture, convenience, and variety.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published, related to the incorporation of ingredients of plant origin, especially cereals and legumes, as a strategy for the development of gluten-free products, with better rheological and texture characteristics, greater nutritional value and sensory quality (Li et al, 2020;Bassinello et al, 2020;Diniz et al, 2020;Chis et al, 2020;Raymundo, Torres & Sousa, 2020).…”
Section: Introductionmentioning
confidence: 99%